Motor function and behaviour across the ALS‐FTD spectrum. (30th July 2015) - De Silva, D.; Hsieh, S.; Caga, J.; Leslie, F. V. C.; Kiernan, M. C.; Hodges, J. R.; Mioshi, E.; Burrell, J. R.
Abstract : Background: Behavioural/functional disturbances, characteristic of frontotemporal dementia (FTD), are also a feature of amyotrophic lateral sclerosis (ALS) and patients with combined ALS and FTD (FTD‐ALS). Aim of the study: To investigate the progression of behavioural disturbances in ALS and FTD using the FTD functional rating scale (FTDFRS). Methods: Patients with ALS, FTD‐ALS and FTD were recruited from specialist clinics. Baseline assessments included the FTDFRS and the ALS functional rating scale–revised (ALSFRS‐R). Baseline assessments were included, as were longitudinal assessments in a proportion of patients. Results: In total, 21 ALS, 12 FTD‐ALS and 14 behavioural variant FTD (bvFTD) patients were included in the study. Moderate or severe behavioural disturbance was common in patients with ALS at baseline (47.6%), although less frequent than in bvFTD patients; patients with FTD‐ALS displayed intermediate impairment. The ALSFRS‐R showed the opposite pattern and did not correlate with the FTDFRS. During the follow‐up period, significant ( P < 0.05) behavioural deterioration was demonstrated in patients with bvFTD and FTD‐ALS, with a trend for decline in patients with ALS ( P = 0.06). Conclusion: Motor disturbance is the primary marker of disease severity in ALS, but behavioural and functional impairment are common, and may decline independently of motor function. As such, the FTDFRS may provide valuable information in the assessment and monitoring of ALS.